The Role of Forensic Medicine Durıng Organ Extraction Process on the Judicial Cases - Beyaztaş, Fatma Yücel; İlhan, Ramazan; Yaman, Sema; Bütün, Celal; Özen, Bahadır; Yıldız, Özlem Kayım (The Bulletin of Legal Medicine, 2014)
When medico-legal cases occurred brain death are potential donor candidates for organ transplantation, various problems concerning forensic medicine, judicial needs and ethics are confronted. In this paper, the problems encountered during organ extraction process in a judicial death case are reported.In the emergency service, physical examination of a case with attempted suicide to the head by firearm, revealed visible brain parenchyma through a bone defect on the right fronto-temporal region, a wound defect on the left frontal region, multiple cranium fractures and brain hemorrhage. The case immediately underwent operation, the bone defects were closed and the wounds were sutured. Approximately one day after the operation, a diagnosis of brain death was made in the intensive case unit. As the case is a potential donor candidate for organ transplantation, an interview with his family members was made, resulting in agreement for organ donation. When the public prosecutor asked to the Forensic Medicine Department for the acceptability of organ extraction, after the evaluation of judiciary and medical records, we decided that the organ extraction would not preclude the determination of the cause of death in this case. After the approval of the public prosecutor, an external examination was made just before organ extraction. Thereafter, the case immediately underwent operation for organ extraction. The autopsy was performed on the deceased, after the operation. In conclusion, it is obvious that, when medico-legal cases occurred brain death are potential donor candidates for organ transplantation, the collaboration of public prosecutors with forensic medicine experts would be beneficial for both the organ extraction and the judicial processes.Key Words: Judicial case; brain death; organ transplantation; autopsy; forensic medicine.
Keywords: judicial case; brain death; organ transplantation; autopsy; forensic medicine